Development of extruded ready-to-eat snacks using pumpkin seed (Cucurbita pepo) and nixtamalized maize (Zea mays) flour blends - Navarro-Cortez, R.O.; Hernández-Santos, Betsabé; Gómez-Aldapa, C.A.; Castro-Rosas, J.; Herman-Lara, Erasmo; Martínez-Sánchez, C.E.; Juárez Barrientos, José Manuel; Antonio Cisneros, Cynthia Magaly; Rodríguez-Miranda, Jesús (Revista Mexicana de Ingeniería Química, 2016)
Extruded ready-to-eat snacks were prepared from flour blends made with pumpkin seed (PSF) and nixtamalized maize (NMF) using a single-screw extruder with a compression screw ratio of 3:1. A central composite rotatable design was used to investigate the e ects of the PSF proportion in formulations (0- 30 g/100 g), feed moisture content (14- 20 g/100 g) and extrusion temperatures (120- 180 °C) on the physical properties like expansion index (EI), bulk density (BD), water absorption index (WAI), water solubility index (WSI), hardness (H), pH and total color di erence ( E). The results indicated that EI, BD and E were significantly a ected by increasing the proportion of PSF and BD, whereas increasing E resulted in an opposite e ect on EI (P<0.05). Temperature significantly negatively a ected (P<0.05) EI and H, while increased moisture content only caused a significant increase (P<0.05) in WAI. Optimal conditions were at an extrusion temperature of 120 °C, feed moisture content of 20 g/100 g and PSF content of 10.36 g/100 g and protein content =11.74 g/100 g. The ready-to-eat snack developed in this research could be considered as a functional food with nutritional and health benefits.
Keywords: Cucurbita pepo; Proceso de extrusión; Harina de maíz; Bocadillos